South African wine farm valuation: A methodical approximation - Smith, Willem (Acta Structilia, 2001)
In recent years obvious changes have taken place regarding the valuation of wine farms (and other farms) in South Africa. The value of the rand declined strongly against other world currencies, for example the American dollar and the pound sterling. Many foreigners used this opportunity to buy farms, especially wine farms, in South Africa. The current poor exchange rate has drastically influenced the value of these farms. Unreason-ably high prices paid for a property destabilise the market and influence the property value of adjacent farms. The poor exchange rate as well as other factors e.g. the location, the state of the infrastructure and the current goodwill, to a large extent influence the final sales price, and thus focus on local property valuation methods.